El Niño meets La Niña – anomalous rainfall patterns in the “traditional” El Niño region of southern Ecuador - Bendix, Jörg; Trachte, Katja; Palacios, Enrique; Rollenbeck, Rütger; Göttlicher, Dietrich; Nauss, Thomas; Bendix, Astrid (ERDKUNDE, 2011)
In this paper, the central Pacific cold event of 2008 and its exceptionally warm conditions in the eastern tropical Pacific are analyzed by using rainfall data of south Ecuadorian meteorological stations, sea surface temperatures in the El Niño3 and 1+2 regions, and simulations with the Weather Research and Forecasting (WRF) model. It can be shown that El Niño-like rainfall conditions with severe inundations occur particularly in the coastal plains of southern Ecuador while a central Pacific cold event prevails. In contrary to previous situations, positive rainfall anomalies as a result of El Niño-like conditions in the El Niño1+2 region during the 2008 La Niña event occurred in both regions, the coastal plains and the highlands, for the first time. A detailed analysis of the ocean-atmosphere system during episodes of heavy rainfall reveals typical El Niño circulation and rainfall patterns as observed during previous El Niño events for the coastal area and La Niña-like conditions for the highlands. The spreading of Pacific instability in the Niño1+2 region to the eastern escarpment of the Andes could be the result of a temporary eastward shift of the Walker circulation. The unusual combination of El Niño-like conditions in the eastern tropical Pacific during a La Niña state in the central Pacific is the newest indicator for an impact mode shift regarding severe rainfall anomalies during El Niño/La Niña events in the traditional El Niño area of southern Ecuador since the end of the last century. Since 2000, El Niño events unexpectedly provide below average rainfall while central Pacific La Niña conditions generate exceptional severe flooding in the normally drier coastal plains. The novel sea surface temperature (SST) anomaly dipole structure between the eastern and central/western tropical Pacific and the weakening of El Niño events since 2000 could be due to natural decadal oscillations in the El Niño background state, the Pacific Decadal Oscillation (PDO). However, the observed atmospheric patterns and the recent increase of the SST anomaly difference between the central and the eastern tropical Pacific resemble structures that also result from climate change simulations.